Strategi Penggunaan Promosi Media Sosial dan Korelasinya dengan Daya Beli Konsumen Secara Berkelanjutan - Nisya Fauziah; Chuzaimah Batubara (Universitas Muhammadiyah Enrekang, 2023)
Advertising through social media has a major impact on consumer purchasing power which is continuously loaded with technological media in this era which is very much used for promotion in the business world. The main objective of this article is to see how social media advertising is utilized with consumer purchasing power in a sustainable manner. This article uses the most recent literature and is also related to the problem being investigated. And this paper also focuses on innovation, resource utilization and risks of social media advertising itself. In addition, we statistically calculate the results of five social media effectiveness measures, namely, brand loyalty, brand preference, brand commitment, brand. association, and buying involvement. And at the end of the article, we provide recommendations for further research and suggestions on how to address the growing interest in this area. And we also promote the impact of this social media advertising and its relationship to consumer purchasing power.